2021
DOI: 10.3390/app11041837
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Exposure to Bisphenol A Alternatives and Its Effects on Reproduction and Thyroid Endocrine System in Zebrafish

Abstract: Bisphenol A (BPA), which is widely used for manufacturing polycarbonate plastics and epoxy resins, has been banned from use in plastic baby bottles because of concerns regarding endocrine disruption. Substances with similar chemical structures have been used as BPA alternatives; however, limited information is available on their toxic effects. In the present study, we reviewed the endocrine disrupting potential in the gonad and thyroid endocrine system in zebrafish after exposure to BPA and its alternatives (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Studies have found that BPA substitutes affect both reproductive and thyroid systems in zebrafish. 97 Prochloraz also induces crosstalk among the HPG, hypothalamic−pituitary−adrenal, and HPT axes in zebrafish. 98…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that BPA substitutes affect both reproductive and thyroid systems in zebrafish. 97 Prochloraz also induces crosstalk among the HPG, hypothalamic−pituitary−adrenal, and HPT axes in zebrafish. 98…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine disruptors may therefore interfere with the entire endocrine system of an individual. Studies have found that BPA substitutes affect both reproductive and thyroid systems in zebrafish . Prochloraz also induces crosstalk among the HPG, hypothalamic–pituitary–adrenal, and HPT axes in zebrafish .…”
Section: Discussionmentioning
confidence: 99%
“…It indicates that endocrine disruption is happening in the case of BP analogues or BPA alternatives as well. 36 BPA induces increased peroxisome proliferators-activated receptor γ (PPARγ) expression, causing downregulation of metabolic enzymes of cytochromes P450 (CYP) family and increasing the lipid accumulation in the cells. 37 Currently, oestrogen deficiency is recognized as a risk factor for hepatic steatosis.…”
Section: B Is Phenol S Endocrine Dis Rup Tion and C Arcinog Enicit Ymentioning
confidence: 99%
“…Its mRNA expression was found to be significantly higher in male zebrafish exposed to BPA, BPS, BPAF and BPF. It indicates that endocrine disruption is happening in the case of BP analogues or BPA alternatives as well 36 . BPA induces increased peroxisome proliferators–activated receptor γ (PPARγ) expression, causing downregulation of metabolic enzymes of cytochromes P450 (CYP) family and increasing the lipid accumulation in the cells 37 .…”
Section: Bisphenols Endocrine Disruption and Carcinogenicitymentioning
confidence: 99%
“…These dummy templates have a chemical structure similar to BPA, which eliminates template leakage and improves sensitivity. Unfortunately, the majority of dummy templates have estrogenic effects, which can lead to secondary contamination that is risky to human health and the environment [13]. As a result, developing a highly selective, environmentally friendly, nontoxic, and nonhazardous dummy template for BPs is critical.…”
Section: Introductionmentioning
confidence: 99%